High‐Performance Li‐O2 Batteries with Trilayered Pd/MnOx/Pd Nanomembranes. Issue 9 (26th May 2015) - Lu, Xueyi; Deng, Junwen; Si, Wenping; Sun, Xiaolei; Liu, Xianghong; Liu, Bo; Liu, Lifeng; Oswald, Steffen; Baunack, Stefan; Grafe, Hans Joachim; Yan, Chenglin; Schmidt, Oliver G.
<x xml:space="preserve">Abstract</x> Trilayered Pd/MnOx/Pd nanomembranes are fabricated as the cathode catalysts for Li‐O2 batteries. The combination of Pd and MnOx facilitates the transport of electrons, lithium ions, and oxygen‐containing intermediates, thus effectively decomposing the discharge product Li2O2 and significantly lowering the charge overpotential and enhancing the power efficiency. This is promising for future environmentally friendly applications.